Differential importance of language components in determining secondary school students' Chinese reading literacy performance. (October 2013) - Leong, Che Kan; Ho, Man Koon; Chang, Jianfang; Hau, Kit Tai
The present study examined pedagogic components of Chinese reading literacy in a representative sample of 1164 Grades 7, 9 and 11 Chinese students (mean age of 15 years) from 11 secondary schools in Hong Kong with each student tested for about 2.5 hours. Multiple group confirmatory factor analyses showed that across the three grade levels, the eight reading literacy constructs (Essay Writing, Morphological Compounding, Correction of Characters and Words, Segmentation of Text, Text Comprehension, Copying of Characters and Words, Writing to Dictation and Reading Aloud), each subserved by multiple indicators, had differential concurrent prediction of scaled internal school performance in reading and composing. Writing–reading and their interactive effects were foremost in their predictive power, followed by performance in error correction and writing to dictation, morphological compounding, segmenting text and copying with reading aloud playing a negligible role. Our battery of tasks with some refinement could serve as a screening instrument for secondary Chinese students struggling with Chinese reading literacy.